First Report of a Cyclops Lamb Associated With a Normal Twin Lamb From Iran - Hossein Hamali; Nader Chador Shabi (The Iranian Journal of Veterinary Science and Technology, 2010)
A four- year-old Moghanian breed ewe was admitted to the large animal veterinary clinic, University of Tabriz due to dystocia. During obstetrical examination, it was revealed that the cervix has been closed firmly and vagina protruded about 5 cm through the vulva (vaginal prolaps). Based on clinical findings and for saving the dam and lamb(s), the cesarean section was done. A normal alive female lamb twin to a monster dead male was delivered. According to the facial deformity, the monster twin was diagnosed as Cyclops lamb. This is the first report of a Cyclops lamb’s giving birth twine to a normal lamb from Iran.